The Knowledge of God's Quid Sit in Dominican Theology: From Saint Thomas to Ferrariensis - Agostini, Igor (American catholic philosophical quarterly, 2019)
In this article I argue that although the prevailing interpretation within the Thomistic contemporary critical literature, claiming the inaccessibility of God's quid sit, is faithful both to Saint Thomas and to John Capreolus's account of Aquinas's doctrine, it is far from being uncontroversial in the first steps of the history of Thomism. A central step in this history is marked by the Parisian Condemnation of 1277, which is at the origin of relevant debate within the Dominican Order on the question of the knowledge of God's quid sit. Aquinas's contemporaries, indeed, interpreted the condemnation of Proposition 214 as a measure taken against Saint Thomas's negative theology, as confirmed by John Capreolus's testimony. Capreolus defends Aquinas, claiming that Saint Thomas's doctrine is not a radical negative theology; in spite of this, he maintains that we cannot know God's quiddity. In the following history of the debate, however, two influential representatives of the Dominican Order, Tommaso de Vio (Cajetanus) and Francesco Silvestri (Ferrariensis) will affirm the accessibility of God's quid sit, restoring an old doctrine by Durand of Saint Pourçain and Hervé of Nédellec.